Effect of exogenous melatonin on salt stress in cucumber: alleviating effect and molecular basis - Tingting Liu; Guoming Xing; Zhifeng Chen; Xijiao Zhai; Xuyang Wei; Chen Wang; Tianmeng Li; Shaowen Zheng (Biotechnology & Biotechnological Equipment, 2022)
AbstractCucumber (Cucumis sativus L.) is sensitive to the salinization of environment. Soil salinization in facility environment affects the yield and quality of cucumber. Melatonin (N-acetyl-5-methoxytryptamine) is an effective free radical scavenger in plants and could effectively alleviate the abiotic stress injury of plants. In this study, we investigated the effect of different concentrations of exogenous melatonin in mitigating salt stress in cucumber and some underlying molecular mechanisms. The results indicated that 100 μmol/L melatonin-treated plants increased significantly the content of the content of ascorbic acid (ASA), proline, glutathione (GSH), polyphenol and flavonoid, and superoxide dismutase (SOD) and peroxidase (POD) activity, soluble protein and sugars. We utilized RNA-seq technology to analyse the transcriptome profile of leaf tissues under M0 and M2 treatments. The analysis identified 699 differentially expressed genes (DEGs) with 506 up-regulated and 193 down-regulated genes. Most of the transcription factors identified were also involved in plant stress defense. Gene Ontology (GO) enrichment analysis of the DEGs showed significant enrichment of 328 GO terms (p ≤ 0.05). Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis showed that the DEGs were significantly enriched in 63 KEGG pathways (p ≤ 0.05). Taken together, these results provided a valuable reference for exploring the mechanism of action of exogenous melatonin in cucumber in saline environment.